MENYOAL TAFSIR IBN ‘ARABI: : MAGNUM OPUS ‘ABD RAZZAQ AL-KASYANI - Darmawan (Sekolah Tinggi Agama Islam (STAI) Sadra, 2017)
This article is aimed to This article discusses about Tafsīr Ibn ‘Arabi. It focuses on describing it and questioning the essence of its writer. The blur of its writer will impact on the precision of the researchers in constracting the figure thought. By an analysis descriptive method and ‘Irfan al-Nazhari it finds that: First, essentially the Tafsīr Ibn ‘Arabi is called Ta'wīlāt al-Kasyani or Ta'wīlāt al-Qur’anal-Hakīm which is written by Syaikh ‘Abd Razzāq al-Kasyani is not written by Ibn ‘Arabi. Second, this book is categorized as al-isyārī al-syuhūdī or al-faidhi and tafsir al-isyārī al-nazhari. Third, ‘Abd Razzāq al-Kasyani is one of the prominent figures of Ibn Arabin thought, commentator works, interpreter and the founder of sufi terminologies works. He is the knower which has much knowledge and being one of prominent writer in the history of Sufi Civilization.